Genomic diversity and differentiation of Alu insertion polymorphisms in a native British and four South Asian migrant populations - Rebekah Beaumont; Liz Akam; Puneetpal Singh; Jasvinder Singh Bhatti; Sarabjit Mastana (Taylor & Francis Group, 2023)
Background Alu insertions are bi-allelic and primate-specific, this makes them a useful marker for studying genetic variation, migration patterns, forensic analyses, paternity, and evolutionary heritage; however, specific population studies are limited. Aim The objective of this study is to document the level and extent of genetic variation at 39 different Alu loci in five populations (British, Indian Punjabi, Indian Gujarati, Pakistani, and Bangladeshi) from the East Midlands region of the UK. Genetic data on migrant populations is currently limited. Subjects and Methods DNA samples (n = 543) were analysed for 39 Alu insertion polymorphisms using specific primers and standard protocols. Data were analysed for population and forensic genetic parameters. Results All studied Alus were polymorphic in the British White population while South Asian migrant populations had a variable number of loci which were monomorphic. Highest heterozygosities and lowest match probabilities were observed in the British sample, while the Bangladeshi sample had the lowest heterozygosity and higher match probability. Conclusion The analysed Alus insertions (TPA25, Ya5NBC123, Ya5NBC182, Ya5NBC241, and Ya5NBC242) are highly polymorphic and variable among migrant populations. These loci could be useful for population genomic and differentiation studies.